ABOUT THE MORPHOGENESIS, DIAGNOSIS AND TREATMENT OF LIVER CIRRHOSIS - Bobonazarov Samariddin Daminovich,; Amonova Gulafzal Uzbekboyevna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Chronic liver disease (CLD) is a neglected epidemic. Cases of early death from this disease are increasing. Along with heart and respiratory diseases, liver diseases are among the top three health problems in Uzbekistan. 50% of patients with CLD are first diagnosed with cirrhosis after emergency care, leading to poor patient outcomes. Traditional care models are based on secondary care when the need is at the community level. Screening patients for the presence of the disease based on population-level risk factors in the community allows early detection of disease when potential reversibility is present.